Members’ Experiences and Perceptions of Community Health Fund Implementation in Tanzania: A Comparative Cross-Sectional Study of Two Improved CHF Models in Dodoma and Kilimanjaro Regions - Adeline Ajuaye; Patrick Develtere (International Journal of Environmental Research and Public Health, 2026)
Background: Community-based health insurance is an important strategy for extending healthcare access and financial protection to informal-sector populations. In Tanzania, the Improved Community Health Fund (iCHF) is implemented through region-specific models that differ in benefit packages, premium arrangements, and provider participation. However, evidence on how members experience these different implementation models remains limited. This study compared members’ experiences and perceptions of CHF implementation in Dodoma and Kilimanjaro, two regions operating different iCHF models. Methods: The study used data from a cross-sectional household survey conducted among 420 CHF-enrolled members in Dodoma and Kilimanjaro in January 2018. Data were collected using a structured, interviewer-administered household questionnaire covering socio-demographic characteristics, CHF enrolment history, registration and premium-payment experiences, benefit-package perceptions, trust in CHF management and community participation, perceived healthcare service quality, and perceived benefits of membership. Data were analyzed using descriptive statistics, cross-tabulations, and Pearson’s chi-square tests to assess regional differences. Results: Members generally reported positive experiences with CHF administration. Most had used their CHF cards, renewal intentions were high, premiums were considered affordable, payment arrangements were convenient, and local CHF management was generally perceived as trustworthy. Statistically significant regional differences were observed in renewal intention, satisfaction with CHF officers, perceived healthcare service quality, and perceived household benefit (p < 0.05). Dodoma respondents reported higher renewal intention and a higher proportion of households benefiting from CHF. The distribution of healthcare-quality ratings also differed significantly (p < 0.001): Kilimanjaro had a higher proportion rating care as excellent (16.1% vs. 2.9%), whereas Dodoma had a higher proportion rating care as good (44.6% vs. 38.9%). Challenges in both regions included limited benefit coverage, additional out-of-pocket payments, long waiting times, and limited perceived advantages of CHF membership. Conclusions: Regional differences were observed in members’ experiences; however, because the regional samples differed socioeconomically and the analysis was not adjusted for potential confounders, these differences should not be attributed to the iCHF models themselves. The findings describe members’ experiences during the 2018 pilot period and should not be interpreted as a direct description of current iCHF performance. The results nevertheless highlight the importance of benefit coverage, service responsiveness, financial protection, and healthcare quality alongside efficient administration.